Pharmacological Interventions for Glucocorticoid-Induced Osteoporosis: An Umbrella Review - Liang, Haodong; Zhao, Jinlong; Tian, Tianzhao (Hormone and Metabolic Research, 2023)
There is still a lack of high-quality evidence-based studies on the efficacy of drug treatment for glucocorticoid-induced osteoporosis (GIOP). The purpose of this umbrella review is to comprehensively evaluate the existing evidence to determine the efficacy and safety of pharmacological interventions for GIOP. We searched PubMed, Embase, and the Cochrane Library for systematic reviews and/or meta-analyses (SRs) of randomized controlled trials (RCTs) aimed at evaluating drug therapy for GIOP. Both the methodological quality and the strength of recommendation of the endpoints included in the SRs were evaluated by using the AMSTAR-2 tool and GRADE system, respectively. Six SRs involving 7225 GIOP patients in 59 RCTs were included in this umbrella review. The results of the methodological quality evaluation showed that 2 high-quality, 2 low-quality and 2 critically low-quality SRs were included. The GRADE evaluation results showed that the quality of evidence and the strength of recommendation of 46 outcome indicators were evaluated in the umbrella review; there were 3 with high-level evidence, 20 with moderate-level evidence, 15 with low-level evidence, and 8 with very low-level evidence. Moderate- to high-level evidence suggests that teriparatide, bisphosphonates, and denosumab can improve the bone mineral density in patients with GIOP. The findings of this umbrella review can enable patients and clinical healthcare professionals to choose the best drug prescription.
Keywords: glucocorticoid-induced osteoporosis; umbrella review; efficacy; safety; pharmacotherapy